Analysis of Teacher's Readiness in Implementing Learning Based on Science Technology Engineering and Mathematical in Children of Early Age - Rini, Ratu Yustika; Syaodih, Ernawulan (International Conference on Elementary Education, 2020)
This essay draws data from several studies that have been carried out some previous research that discusses the teaching beliefs in Science in Engineering and Mathematical Technology (STEM). This essay aims to express some opinions of early childhood education teachers about implementing STEM in terms of high and low economic backgrounds. This essay uses a systematic literature review method. A total of 8 related journal articles that examine STEM in children and articles taken from 2010 to 2018 are used as sources to be reviewed. The belief of early childhood teachers in implementing a learning innovation is still rarely done, this arises because there is still a lack of understanding of teachers related to learning innovations that always develop in accordance with the times. Teachers' teaching experience and their awareness of the importance of science, technology, engineering and mathematics and the way in which science, technology, engineering and mathematics teaching are integrated play different roles in teaching in the classroom. The results of the analysis carried out there are differences in beliefs and awareness revealed between teachers in schools with a high economic background and a low economy related to teacher beliefs in implementing STEM learning in early childhood. The findings of this analysis support the need for professional improvement that can increase teacher understanding of the importance of STEM in early childhood